Sovereign spreads in the Eurozone: Is market discipline working? - Igor Esteban Zuccardi (Banco de México, 2015)
This paper studies the behavior of sovereign spreads of countries in the European Monetary Union (EMU) and their apparent disconnection with country-specific fundamentals before the 2008- 2013 debt crisis. We test three characteristics of spreads: i) a change in the level of spreads, ii) a weak link between spreads and macroeconomic fundamentals, and iii) a reduction in the cross-country variance of spreads. We find that, in comparison to economies from other regions, spreads from EMU members are lower, the relationship of spreads with variables like fiscal balance, public debt, and GDP growth rate is weaker, and their cross-country variance is statistically lower than the cross-country variance of spreads from non-EMU countries between 1999 and 2005. The results are consistent with the existence of creditor moral hazard in the EMU's sovereign bond market before the crisis.
Keywords: F33; G12; 330; European Monetary Union; Sovereign Debt Risk; Investor (Creditor) Moral Hazard